Immunity, Sex Hormones, and Environmental Factors as Determinants of COVID-19 Disparity in Women - Rehman, Suriya; Ravinayagam, Vijaya; Nahvi, Insha; Aldossary, Hanan; Al-Shammari, Maha; Amiri, Mai Saad Al; Kishore, Uday; Al-Suhaimi, Ebtesam A. (Frontiers in Immunology, 2021)
The current coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome virus 2 (SARS-CoV-2), has resulted in a major global pandemic, causing extreme morbidity and mortality. Few studies appear to suggest a significant impact of gender in morbidity and mortality, where men are reported at a higher risk than women. The infectivity, transmissibility, and varying degree of disease manifestation (mild, modest, and severe) in population studies reinforce the importance of a number of genetic and epigenetic factors, in the context of immune response and gender. The present review dwells on several contributing factors such as a stronger innate immune response, estrogen, angiotensin-converting enzyme 2 gene, and microbiota, which impart greater resistance to the SARS-CoV-2 infection and disease progression in women. In addition, the underlying importance of associated microbiota and certain environmental factors in gender-based disparity pertaining to the mortality and morbidity due to COVID-19 in women has also been addressed.